Storytelling in Pregnancy and Childbirth: An Integrative Review of the Literature - Zahra Mahdavi; Leila Amiri-Farahani; Sally Pezaro (Journal of Pregnancy)
Background and Objectives. Storytelling is a common and popular way of conveying events, culture, ideas, and information. Stories have been used in various sciences to convey a particular concept that is influenced by the culture of individuals. Storytelling about childbirth may be useful to women in a number of ways. The objective of this review was to synthesize existing literature in relation to storytelling in the context of childbirth to inform future childbirth education programmes, interventions, and research. Methods. An integrative review of the literature was conducted, including peer-reviewed articles published between 2001 and 2022. The following databases were used to search for relevant studies: PubMed, CINAHL, PsycINFO, Web of Science, Ovid, Google Scholar, ScienceDirect, Cochrane Library, Magiran, Irandoc, and SID. A process of thematic synthesis was used to make sense of the data extracted. Results. Whilst 21 studies were retrieved, only 12 were relevant and thus met the inclusion criteria set. Two themes were identified from our thematic synthesis: (1) effects of childbirth storytelling on the storyteller and (2) effects of childbirth storytelling on the listener of the story. Subthemes included “reducing fear of childbirth,” “transferring information and raising awareness in line with community culture,” and “adjusting expectations.” Conclusion. The use of storytelling can be used as an effective method in educational interventions during pregnancy and childbirth. Due to limited high-quality intervention studies in this field, future studies could usefully be more robustly designed and incorporate digital storytelling methods to inform future directions.